Effects of Custom-made Mouthguards on Cardiopulmonary Exercise Capacity - Lässing, Johannes; Schulze, Antina; Kwast, Stefan; Falz, Roberto; Vondran, Maximilian; Schröter, Thomas; Borger, Michael; Busse, Martin (International journal of sports medicine, 2021)
The importance of using mouthguards as well as their low acceptance rate have been demonstrated. The aim of this study was to investigate the influence of customized mouthguards on hemodynamics.. This randomized crossover study used data from 13 subjects (23.5±1.4 years). The cardiopulmonary and metabolic parameters were observed during ergometer tests without mouthguard (control) in comparison to two types of mouthguards (with and normal without breathing channels). Maximum ventilation was significantly decreased with the normal mouthguard (113.3±30.00 l ∙ min ) in contrast to the mouthguard with breathing channels (122.5±22.9 l ∙ min ) and control (121.9±30.8 l ∙ min ). Also the inspiration time was longer when using the normal mouthguard (0.70±0.11 s) compared to the mouthguard with breathing channels (0.63±0.11 s) and control (Co 0.64±0.10 s). Lactate was also increased under the influence of the mouthguard with breathing channels (10.72±1.4 mmol ∙ l ) compared to the control (9.40±1.77 mmol ∙ l ) and the normal mouthguard (9.02±1.67 mmol ∙ l ). In addition, stroke volume kinetics (p=0.048) and maximum heart rates (p=0.01) show changes. Despite equal levels of oxygen uptake and performances under all three conditions, the use of mouthguards showed differences in cardiopulmonary parameters. The use of mouthguards during exercise does not affect physical performance and can be recommended for injury prevention.